Wheel-rail contact force measurement using strain gauges and distance lasers on a scaled railway vehicle. (April 2020) - Urda, Pedro; Muñoz, Sergio; Aceituno, Javier F.; Escalona, José L.
Highlights: A scaled dynamometric wheelset with two instrumentation technologies is presented. Two different force calculation algorithm have been developed. The dynamometric wheelset has been calibrated on a scaled calibration test bench. Several test have carried out on a 5 inch wide scaled track. The measured lateral and vertical forces have been compared with simulations. Abstract: In this paper, a 1 : 10 scaled dynamometric wheelset is presented. It has been equipped with two different technologies: strain gauges and distance lasers. The first one is based on the measurement of the wheel deformation with strain gauges and the second one on the measurement of the wheel web deflection with high precision distance lasers. The dynamometric wheelset has been carefully calibrated on a scaled calibration test bench. Several tests have been carried out on a 5-inch gauge scaled track to validate the dynamometric wheelset performance. The measured lateral and vertical forces of each experiment have been compared with an estimation drawn from a computational model of the scaled vehicle. A good accordance between the measurement and the model based estimation is achieved.